Greeting From Trinidad, B.W.I. - Thomas, H.O. (H.O. Thomas, 2009)
Description on the back of the postcard reads "Greeting From Trinidad, B.W.I. Maracas bay is a favourite Bathing Resort sheltered on all sides by towering green hills".
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bays--Trinidad and Tobago; Maracas Bay